PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V UPTD SD NEGERI 122365 PEMATANGSIANTAR - Geovani Malinda Sinaga; Minar T. Lumban Tobing; Jon Roi Tua Purba (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to determine the effect of the role playing learning model on the Pancasila education learning outcomes of class V UPTD students at SD Negeri 122365 Pematangsiantar. This research uses a quantitative research method with "Pre-Experimental Design". One group pre-test post-test form was carried out at UPTD SD Negeri 122365 Pematangsiantar on class V students with a population of 24 students and a sample of 24 students. This data collection technique uses tests twice, namely pretest-posttest. The data was processed using statistical analysis techniques, from the results of data analysis a significant level of 0.00 < probability (0.05) and tcount = 29.00 > ttable = 1.71 were obtained. So it was concluded that Ho was rejected and Ha was accepted, which means "There is an influence of the Role Playing learning model on the Pancasila Education Learning Outcomes of Class V UPTD Students at SD Negeri 122365 Pematangsiantar".